1995
DOI: 10.1073/pnas.92.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Virus-mediated or transgenic suppression of a G-protein alpha subunit and attenuation of fungal virulence.

Abstract: Strains of the chestnut blight fungus Cryphonectria parasitica harboring RNA viruses of the genus Hypovirus exhibit significantly reduced levels of virulence (called hypovirulence). The accumulation of a heterotrimeric GTP-binding protein (G protein) a subunit of the G1 class was found to be reduced in hypovirus-containing C. parasitica strains. Transgenic cosuppression, a phenomenon frequently observed in transgenic plants, reduced the accumulation of this cr subunit in virus-free fungal strains. Significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 33 publications
(25 reference statements)
2
122
0
1
Order By: Relevance
“…However, the cpmk2 phenotypes of changes in growth pattern related to culture conditions (liquid vs solid media) and a complete lack of conidiation are unusual. Similar phenotypes have been observed previously in strains with mutations in genes related to G-proteins (Choi et al, 1995;Segers & Nuss, 2003). The G-proteincoupled MAPK cascade that responds to mating pheromones in S. cerevisiae is a good example of G-proteins activating a downstream MAPK pathway.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, the cpmk2 phenotypes of changes in growth pattern related to culture conditions (liquid vs solid media) and a complete lack of conidiation are unusual. Similar phenotypes have been observed previously in strains with mutations in genes related to G-proteins (Choi et al, 1995;Segers & Nuss, 2003). The G-proteincoupled MAPK cascade that responds to mating pheromones in S. cerevisiae is a good example of G-proteins activating a downstream MAPK pathway.…”
Section: Discussionsupporting
confidence: 63%
“…Mutations related to reduced conidiation, pigmentation and vegetative growth have been reported in several studies of C. parasitica signal-pathway-related genes (Zhang et al, 1993;Choi et al, 1995;Kim et al, 2002). However, the cpmk2 phenotypes of changes in growth pattern related to culture conditions (liquid vs solid media) and a complete lack of conidiation are unusual.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The double-stranded RNA viruses HAV1 and CHV1-713, which attenuate virulence, have also provided a unique tool with which to examine virulence mechanisms in this organism (214). G proteins involved in signal transduction have been identified (49,88,127,128,292). C. parasitica G proteins regulate growth and virulence in C. parasitica.…”
Section: Cryphonectria Parasiticamentioning
confidence: 99%
“…To date, only a few studies have examined the influence of the G protein or MAPK signaling on extracellular enzyme secretion. Wang and Nuss [29] first reported that the induction of CHB-1, a cellobiohydrolase gene from Cryphonectria parasitica, is mediated through a G-protein α subunit linked signal transduction pathway shown earlier to be required for fungal pathogenesis [43]. In saprophytic and pathogenic fungi, it is known that extracellular glycan hydrolases are induced by their substrate and repressed by glucose at the level of gene expression (reviewed by a Extracellular CMCase enzymatic activity was measured for liquid cultures grown on 1% CMC and 0.1% maltose containing minimal medium.…”
Section: Discussionmentioning
confidence: 99%